Efficacy and safety of rolapitant for prevention of chemotherapy-induced nausea and vomiting over multiple cycles of moderately or highly emetogenic chemotherapy. (April 2016) - Rapoport, Bernardo; Schwartzberg, Lee; Chasen, Martin; Powers, Dan; Arora, Sujata; Navari, Rudolph; Schnadig, Ian
Abstract: Objective: Rolapitant, a novel neurokinin-1 receptor antagonist (RA), was shown to protect against delayed chemotherapy-induced nausea and vomiting (CINV) during the first cycle of moderately emetogenic chemotherapy (MEC) or highly emetogenic chemotherapy (HEC) in randomized, double-blind trials. This analysis explored the efficacy and safety of rolapitant in preventing CINV over multiple cycles of MEC or HEC. Patients and methods: Patients in one phase III MEC, one phase II HEC, and two phase III HEC clinical trials were randomized to receive oral rolapitant (180 mg) or placebo in combination with a 5-hydroxytryptamine type 3 RA and dexamethasone. Regardless of response in cycle 1, patients could continue the same antiemetic treatment for up to six cycles. On days 6−8 of each subsequent chemotherapy cycle, patients reported the incidence of emesis and/or nausea interfering with normal daily life. Post hoc analyses of pooled safety and efficacy data from the four trials were performed for cycles 2–6. Results: Significantly more patients receiving rolapitant than control reported no emesis or interfering nausea (combined measure) in cycles 2 ( p = 0.006), 3 ( p < 0.001), 4 ( p = 0.001), and 5 ( p = 0.021). Over cycles 1−6, time-to-first emesis was significantly longer with rolapitant than with control ( p < 0.001). The incidence of treatment-related adverse events during cycles 2–6 was similar in rolapitant (5.5%) and control (6.8%) arms. No cumulative toxicity was observed. Conclusions: Over multiple cycles of MEC or HEC, rolapitant provided superior CINV protection and reduced emesis and nausea interfering with daily life compared with control and remained well tolerated. Highlights: Pooled data from randomized phase II and III trials of rolapitant were analysed. Rolapitant provided chemotherapy-induced nausea and vomiting control over multiple cycles of emetogenic chemotherapy. Rolapitant was well tolerated over multiple cycles of emetogenic chemotherapy.